Anti-Corruption Reforms in the Philippines: Quo Vadis? - Mendoza, Ronald U (Archīum Ateneo, 2025)
This article reviews the state of anti-corruption efforts in the Philippines by outlining a typology of corruption and evaluating the country’s progress on these different fronts. Notwithstanding recent gains, the country appears stuck in its anti-corruption efforts. While reforms have managed to advance economic growth, corruption nevertheless continues to undermine private sector investments in key economic sectors and geographic regions associated with high poverty, as well as weakens public goods provision. Corruption de facto erodes the inclusivity of economic growth gains, which eventually contributes to imbalanced growth and inequality. Policy responses, therefore, need to consider the multi-faceted nature and implications of corruption and address its root causes. Reforms to improve competition in the economic and political spheres could help address some of the underlying features of rent-seeking behaviour and corruption. Given how these reforms run into deep political economy issues, a clear theory of change is necessary, touching on both the market economy and the political system.